A Contrastive Analysis of Imperative Sentences in English and Galela Language at Sabatai Tua Village - balqis husain; Fahmi Djaguna; Raveli A Redjeb (Journal of English Education and Linguistics, 2020)
Aim of this research was analyzing the sorts of imperative sentences in English and Galela Language and describing imperative sentences markers in English and Galela Language. The method of this research was qualitative method by using descriptive design. The method in collecting data was documentation, interview, and observation. The analyzing of the data used contrastive analysis and descriptive. The procedure of analysis was finding the similarities of type and marker. The result of analysis presented that English and Galela language had similarity of type; they were positive and negative, but different in markers. The marker of imperative Sentences in Galela language was signed by word of wa, e, upa, hino, and sufix -si. Hence it can be concluded that imperative sentences in English and Galela language were partly correspondence.